The Effect of Compensation and Job Environment on Employee Loyalty through Job Satisfaction as an Intervening Variable - Devi Christianti Yusuf; Djabir Hamzah; Ria Mardiana Yusuf (Magister Management, Hasanuddin University, 2020)
This study aims to determine the effect of compensation and job environment on job satisfaction, the effect of compensation, and job environment on employee loyalty, the effect of job satisfaction on employee loyalty. It is also intended to analyze the effect of compensation and job environment on employee loyalty, through job satisfaction as an intervening variable. This study uses a path analysis model. The sample in this study was 62 permanent employees of the BNI Makassar Branch. The data in this study were obtained by distributing questionnaires. The results showed that the compensation and job environment had a significant effect on job satisfaction. Further, the research indicates that compensation, job environment, and job satisfaction have a positive and significant effect on employee loyalty. The result also found that job environment has a significant effect on employee loyalty through the job satisfaction variable as an intervening. Job satisfaction has a significant effect on employee loyalty and compensation has a significant effect on employee Loyalty through the job satisfaction variable as an intervention.